2012
DOI: 10.1007/s00198-012-1983-0
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal health in adult patients with classic galactosemia

Abstract: Bone density in adults with galactosemia is low, indicating the potential for increased fracture risk, the etiology of which appears to be multifactorial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Decreased bone mineral density has been consistently observed in galactosaemia patients (Rubio-Gozalbo et al 2002;Panis et al 2004;Waisbren et al 2012;Batey et al 2013;Coss et al 2013;Doulgeraki et al 2014). Decreased bone metabolism has been suggested as the mechanism of reduced bone mineral density in galactosaemia as well as abnormal galactosylation of the collagen matrix (Kaufman et al 1993).…”
Section: Congenital Disorders Of Glycosylationmentioning
confidence: 99%
“…Decreased bone mineral density has been consistently observed in galactosaemia patients (Rubio-Gozalbo et al 2002;Panis et al 2004;Waisbren et al 2012;Batey et al 2013;Coss et al 2013;Doulgeraki et al 2014). Decreased bone metabolism has been suggested as the mechanism of reduced bone mineral density in galactosaemia as well as abnormal galactosylation of the collagen matrix (Kaufman et al 1993).…”
Section: Congenital Disorders Of Glycosylationmentioning
confidence: 99%
“…The first report of an association between CG and decreased bone mass dates back to 1993 (Kaufman et al 1993) and a bone mineral density (BMD) Z-score more than two standard deviations (SD) below the mean was found in 25-30% of adult patients (Waisbren et al 2012;Batey et al 2013). Thorough evaluation of the frequency and severity of impaired bone health in CG patients, compared to the non-galactosemia population, is crucial for determining its extent and relevance for patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that body weight and body mass index (BMI) correlate with bone mass in patients with classic galactosemia, emphasizing the need for monitoring caloric intake in this group (Batey et al 2013). Evaluation of food records or food frequency questionnaires, preferably by a nutritionist, can be used to determine a patient's general nutrition status and to assess the completeness of a patient's diet.…”
Section: Dietary Evaluation and Bone Metabolism Markersmentioning
confidence: 98%
“…Decreased bone mass is frequently encountered in classic galactosemia (OMIM 230400), an inborn error of galactose metabolism (Kaufman et al 1993;Rubio-Gozalbo et al 2002;Panis et al 2004;Jumbo-Lucioni et al 2012;Waisbren et al 2012;Batey et al 2013;Coss et al 2013). This decrease in bone mass is most prominent in adults, but is already seen in prepubertal children (Kaufman et al 1993;Rubio-Gozalbo et al 2002;Panis et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation